2018
DOI: 10.17116/jnevro20181187125
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke rehabilitation training with a brain-computer interface: a clinical and neuropsychological study

Abstract: During treatment, there was an improvement in neurophysiological parameters in both groups, which was more pronounced in patients treated with cytoflavin: their P300 amplitude increased by1.3 times in the left hemisphere (from 9.21 (8.36, 10.11) to 12.41 (10.23, 13.37 μV) and 1,7 times in the right hemisphere (from 6.48 (5.26, 7.35) to 11.04 (9.29, 12.18) μV). Our study confirms the advisability of using drugs that have complex cytoprotective and energy-correcting mechanism in patients with cognitive impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Nolfe [24] found that BCI technology based on P300 components could predict the degree of recovery of speech disorder, and the study results showed that the amplitude of P300 was reduced in patients with speech disorder. On this basis, Kleih [25]used the P300-BCI spelling system to assess the language function of patients with speech disorder after stroke. The results showed that 4 stroke patients with speech disorder could successfully communicate with the matching speller after P300-BCI rehabilitation training, and the accuracy rate was 100%.…”
Section: Application Of Bci Technology In Speech Rehabilitation Of St...mentioning
confidence: 99%
“…Nolfe [24] found that BCI technology based on P300 components could predict the degree of recovery of speech disorder, and the study results showed that the amplitude of P300 was reduced in patients with speech disorder. On this basis, Kleih [25]used the P300-BCI spelling system to assess the language function of patients with speech disorder after stroke. The results showed that 4 stroke patients with speech disorder could successfully communicate with the matching speller after P300-BCI rehabilitation training, and the accuracy rate was 100%.…”
Section: Application Of Bci Technology In Speech Rehabilitation Of St...mentioning
confidence: 99%
“…Results showed that the recognition accuracy of patients exposed to mixed BCI was significantly higher than that of those exposed to single P300 (P < 0:05) or MI (P < 0:01) BCI alone. [81,83,85,91], there are significant improvements in multiple domains of cognitive impairment, including executive ability [83,89], language ability [84], attention [87,92], visuospatial ability [91,93], and memory [85,[94][95][96]. One of the other two articles showed that mental fatigue state influenced the assessment and performance of BCI [88], while the others showed that brain-computer interface rehabilitation training was ineffective in patients after stroke.…”
Section: Signal Acquisition Andmentioning
confidence: 99%
“…Nolfe et al [117] suggested that P300 may predict aphasia recovery, and studies have found that the amplitude of P300 decreases in aphasia patients. On this basis, Kleih [84] used the P300-BCI spelling system to assess language functioning in patients with poststroke aphasia. The experiment included five patients with aphasia after stroke.…”
Section: Memory Functionmentioning
confidence: 99%
See 2 more Smart Citations